A simple micro-ELISA method for the assay of antithyroglobulin autoantibodies in human serum. Issue 9 (September 1981) - Goodburn, Richard; Williams, David L; Marks, Vincent
Abstract : An indirect, enzyme-linked immunosorbent assay is described for the assay of thyroid autoantibodies, particularly those directed against thyroglobulin. The method is specific, sensitive and precise, and may be automated. The results are shown to correlate well with those obtained by the haemagglutination method.